Analysis of Upwelling Parameters when the El Nino Southern Oscillation (ENSO) Occurred in the Halmahera Sea - Marthinus, Libertinus; Avrionesti, Avrionesti; Haryanto, Yosafat Donni; Qomariyatuzzamzami, Latifah Nurul (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Upwelling events that occur in the Halmahera Sea are influenced by the El Nino Southern Oscillation (ENSO). Upwelling can cause sea surface temperatures to be lower than normal, affecting the potential of fishery resources in the region. The purpose of this study was to determine the conditions of sea surface temperature, chlorophyll-a content, salinity, and upwelling conditions when viewed from the parameters of chlorophyll-α content and sea surface temperature when El Nino was strong, El Nino was weak, La Nina was strong, and La Nina weak and in normal conditions in the Halmahera Sea region. The data used in this study include the Oceanic Nino Index, sea surface temperature, salinity, and chlorophyll-α content during the 2010–2019 period. A quantitative descriptive research type is used by filtering ENSO data to determine when ENSO occurred, then visualizing the data in each parameter and analyzing it. The results of this study show that upwelling is known to occur in the northern to western parts of the Halmahera Sea. When the El Nino phase is vital, the upwelling parameter changes, the sea surface temperature decreases to 27.1⁰C, the chlorophyll-α content increases to 0.70 mg/m3 compared to the normal phase, and the upwelling intensity changes.